Disparitas Pidana Putusan Hakim Atas Perkara PidanaAnak Dalam Perspektif Perlindungan Hak-Hak Anak (Studi Kasus Pengadilan Negeri Boyolali Tahun 2009-2013 - Mulyohadi, Agus Maksum, Dr. Aidul Fitriciada Azhari, SH., M.Hum, Dr. Nurhadiantomo (2015)
The verdict of judge in the cases of crime committed by child practically goes through criminalization disparity. Therefore, the matter of verdict pronouncement is important not only for the judges and the judicial process, but also the whole legal process, particularly in the law enforcement. The objective of this research is to investigate the cause factors, impact, and model of criminalization policy with the existence of criminalization disparity in the cases of crime committed by child. This research used the qualitative method with empirical juridical approach. The data of this research were gathered through interview and library research and analyzed. The results of this research are as follows: (1) there are two cause factors which causes the criminalization disparity to have happened in the cases of crime committed by child, namely: internal factor which comes from the judges themselves and external factor which comes from either the law and legislation itself or the doer/defendant; (2) the criminalization disparity in the cases of crime committed by child is going to bring about negative impacts. Such impacts are as follows: a) the convict feels to be harmed due to such verdict of judge if the convict makes comparison to another convict sentenced with lighter sentence; b) the convict sentenced with lighter sentence is going to assume that breaking the law is not scary due to the light sentence; and c) the people who seek justice will feel discontent which eventually causes the trust of the people in the penal judicial system to disappear; and (3) the criminalization judicial system in the cases of crime committed by child can be made by creating a criminalization guidance